Symptom persistence despite improvement in cardiopulmonary health -- Insights from longitudinal CMR, CPET and lung function testing post-COVID-19 - Cassar, MP; Tunnicliffe, EM; Petousi, N; Lewandowski, AJ; Xie, C; Mahmod, M; Samat, AHA; Evans, RA; Brightling, CE; Ho, L-P; Piechnik, SK; Talbot, NP; et al. (Elsevier, 2021)
Background The longitudinal trajectories of cardiopulmonary abnormalities and symptoms following infection with coronavirus disease (COVID-19) are unclear. We sought to describe their natural history in previously hospitalised patients, compare this with controls, and assess the relationship between symptoms and cardiopulmonary impairment at 6 months post-COVID-19. Methods Fifty-eight patients and thirty matched controls (single visit), recruited between 14th March - 25th May 2020, underwent symptom-questionnaires, cardiac and lung magnetic resonance imaging (CMR), cardiopulmonary exercise test (CPET), and spirometry at 3 months following COVID-19. Of them, forty-six patients returned for follow-up assessments at 6 months. • View related content for this article Findings At 2-3 months, 83% of patients had at least one cardiopulmonary symptom versus 33% of controls. Patients and controls had comparable biventricular volumes and function. Native cardiac T1 (marker of fibroinflammation) and late gadolinium enhancement (LGE, marker of focal fibrosis) were increased in patients at 2-3 months. Sixty percent of patients had lung parenchymal abnormalities on CMR and 55% had reduced peak oxygen consumption (pV̇O2) on CPET. By 6 months, 52% of patients remained symptomatic. On CMR, indexed right ventricular (RV) end-diastolic volume (-4·3 mls/m2, P=0·005) decreased and RV ejection fraction (+3·2%, P=0·0003) increased. Native T1 and LGE improved and was comparable to controls. Lung parenchymal abnormalities and peak V̇O2, although better, were abnormal in patients versus controls. 31% had reduced pV̇O2 secondary to symptomatic limitation and muscular impairment. Cardiopulmonary symptoms in patients did not associate with CMR, lung function, or CPET measures. Interpretation In patients, cardiopulmonary abnormalities improve over time, though some measures remain abnormal relative to controls. Persistent symptoms at 6 months post-COVID-19 did not associate with objective measures of cardiopulmonary health. Funding The authors’ work was supported by the NIHR Oxford Biomedical Research Centre, Oxford British Heart Foundation (BHF) Centre of Research Excellence (RE/18/3/34214), United Kingdom Research Innovation and Wellcome Trust. This project is part of a tier 3 study (C-MORE) within the collaborative research programme entitled PHOSP-COVID Post-hospitalization COVID-19 study: a national consortium to understand and improve long-term health outcomes, funded by the Medical Research Council and Department of Health and Social Care/National Institute for Health Research Grant (MR/V027859/1) ISRCTN number 10980107.